Carbon Nanotubes Modified With Au for Electrochemical Detection of Prostate Specific Antigen: Effect of Au Nanoparticle Size Distribution - Quintero-Jaime, Andrés Felipe; Berenguer-Murcia, Ángel; Cazorla-Amorós, Diego; Morallón, Emilia (Frontiers in Chemistry, 2019)
Different functionalized Multi-Wall Carbon Nanotube and gold nanoparticles (AuNPs) were synthesized as biosensor electrodes. These materials have been applied to the detection of the Prostate Specific Antigen (PSA). The synthesis of AuNPs was carried out using polyvinylpyrrolidone (PVP) as protecting agent. The PVP/Au molar ratio (0.5 and 50) controls the nanoparticle size distribution, obtaining a wide and narrow distribution with an average diameter of 9.5 nm and 6.6 nm, respectively. Nanoparticle size distribution shows an important effect in the electrochemical performance of the biosensor, increasing the electrochemical active surface area (EASA) and promoting the electron-transfer from the redox probe (Ferrocene/Ferrocenium) to the electrode. Furthermore, a narrow and small nanoparticle size distribution enhances the amount of antibodies immobilized on the transducer material and the performance during the detection of the PSA. Significant results were obtained for the quantification of PSA, with a limit of detection of 1 ngml-1 and sensitivities of 0.085 and 0.056 µA∙mL∙ng-1 for the two transducer materials in only 5 minutes of detection.